HIRUK PIKUK PEMILIHAN KEPALA DAERAH (STUDI KASUS : PEMILIHAN WALIKOTA SAMARINDA 2015) - Salasiah Salasiah (Prodi Ilmu Administrasi Negara, 2019)
The the general aims of the Political party are to get the national ideas as written in preambule of the Republic Indonesia 1945 Constitution ,(2).To develop the democrcy life based on Pancasila and to glorify the soveirinity of the people the united of the Indonesia Republic .Based on those discription above so the objective of this research is to know the preparation of the Political Party to Appoint the candidate of the Mayor and his Vice in Samarinda .The proble is who the competitor is .The location of it is in Samarinda and the method is qualitative by taking the news from Kaltimpost daily news based on the regulation of Political Party and Regional Decree.The results are (1).The candidates are one pair only,(2).The competitors like PDIP ,PAN and others still doing coordination (3).The Condition of Samarinda while facing General Election is condusive . The suggestions are (1).The local government of Samarinda has to keep the city condusive ,(2).It has to arrange the decree of one pair of candidate ,(3).The other political Party as the promotors have coordinate as soon as possible in order to not stagnant